Heterochromatin, HP1 and methylation at lysine 9 of histone H3 in animals. - Cowell, I.G.; Aucott, R.; Mahadevaiah, S.K.; Burgoyne, P.S.; Huskisson, N.; Bongiorni, S.; Prantera, G.; Fanti, L.; Pimpinelli, S.; Wu, R.; Gilbert, D.M.; Shi, W.; et al. (Chromosoma, 2002)
We show that methylated lysine 9 of histone H3 (Me9H3) is a marker of heterochromatin in divergent animal species. It localises to both constitutive and facultative heterochromatin and replicates late in S-phase of the cell cycle. Significantly, Me9H3 is enriched in the inactive mammalian X chromosome (Xi) in female cells, as well as in the XY body during meiosis in the male, and forms a G-band pattern along the arms of the autosomes. Me9H3 is a constituent of imprinted chromosomes that are repressed. The paternal and maternal pronuclei in one-cell mouse embryos show a striking non-equivalence in Me9H3: the paternal pronucleus contains no immunocytologically detectable Me9H3. The levels of Me9H3 on the parental chromosomes only become equivalent after the two-cell stage. Finally, we provide evidence that Me9H3 is neither necessary nor sufficient for localisation of heterochromatin protein 1 (HP1) to chromosomal DNA.